Rainfall Erosivity Analysis of Soil Conservation Research Centre, Vasad (Gujarat) - Singh, A.; Shah, C. M.; Kamannavar, H. K. (Indian Forester, 1976)
Sixteen years of rainfall data of self recording raingauge available at Soil Conservation Research Demonstration and Training Centre, Vasad (Gujarat) have been analysed with regard to its erosivity. Average annual erosivity indicated in the form or EI30 and KE>25 mm was found as 519.3 and 7509.EI30 values have been discussed on weekly basis for the months of June, July, August and September in relation to hazards responsible for soil erosion.